Beginning SQL Server for Developers - Dewson, Robin (Apress, 2015)
Beginning SQL Server for Developers is for those people who see themselves as becoming either developers, database administrators, or a mixture of both, but have yet to tread that path with SQL Server. This edition of my book is for readers who wish to learn and develop on either the free version of SQL Server, SQL Server Express, or with either the trial or licensed versions of SQL Server...